Learn Ethereum : a practical guide to help developers set up and run decentralized applications with Ethereum 2.0 - Wu, Xun (Writer on Blockchain); Zou, Zhihong; Song, Dongying (Packt Publishing Ltd., 2023)
Ethereum is a blockchain-based, decentralized computing platform that allows you to run smart contracts. With this book, you’ll discover the latest Ethereum tools, frameworks, wallets, and layer 2, along with setting up and running decentralized applications for the complete, end-to-end development experience. Learn Ethereum, 2nd Edition is a comprehensive overview of the Ethereum ecosystem, exploring its concepts, mechanisms, and decentralized application development process. You’ll delve into Ethereum's internals, technologies, and tools, including Ethereum 2.0 and the Ethereum Virtual Machine (EVM), gas, and its account systems. You’ll also explore Ethereum's transition to proof of stake, L1/L2 scaling solutions, DeFi protocols, and the current marketplace. Additionally, you’ll learn about EVM-compatible blockchains, connectivity techniques, and advanced topics such as sharding, off-chain scaling, DAOs, Metaverse, and NFTs. By the end of this book, you’ll be well-equipped to write smart contracts and develop, test, and deploy DApps using various tools, wallets, and frameworks.